Analisis Strategi Optimalisasi Pengembangan Wisata Alam dengan Sistem Informasi Geografis di Kecamatan Dlingo, Kabupaten Bantul Provinsi DIY - Susanti, Anita Tri; , Agus Anggoro Sigit, M.Si, M.Sc (2017)
Dlingo subdistrict has many nature tourism object to develop. At least there is 18 nature tourism object that located in Dlingo subdistrict. But, this potential seems haven't develop by the local goverment yet. Goal of this research is identification of nature tourism potential using SIG, identification of nature tourism management and analyzing an optimalization strategy to develop nature tourism object in Dlingo subdistrict. This research using survey methode. Population in this research is nature tourism in Dlingo subdistrict. Sampling methode in this research using purposive sampling. Result of this research is knew that Dlingo has 3 potential grade. High potential tourism object consist of 7 object, middle potential tourism object is 8 object and 3 object as a lowest grade tourism potential. From 18 tourism object that located in Dlingo subdistrict, there are 2 kind of managemen caused by land ownership. The land ownership of tourism object is a state land and private land. Based on tourism potential grade, optimalisation strategy tourism development is have 3 variety. Optimalisation strategy on high potential tourism is 1) make a tourism planning using object tourism identity, 2) promotion, 3) implement environmental principle, and 4) make evacuation route. Optimalisation strategy on middle potential tourism is 1) make an identity tourism tourism, 2) repairing infrastructure, 3) promotion and 4) make evacuation route. Optimalisation strategy on lowest potential tourism is 1) make an identity tourism tourism, 2) developing infrastructure, 3) promotion, 4) management planning if a tourism object is not used as a tourism activity, 5) make evacuation route and training about disaster respons.